Penggunaan Deksametason pada Pasien COVID-19: Systematic Review dan Meta-analisis - Mardhiyyah, Cut Ainul; Setiawan, Didik; Dhiani, Binar Asrining (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
COVID-19 is associated with disseminated lung damage in patients, Dexamethasone can reduce lung injury caused by inflammation and there reduce the progression to respiratory failure and prevent death. This systematic review aimed to determine the benefits and safety of Dexamethasone in COVID-19 treatment. The study was performed by a comprehensive literature search which were published in several databases i.e., PubMed, Science Direct, VHL Regional Portal, and ClinicalTrials.gov within the search time of 28 November 2020. Inclusion criteria were articles on the study on COVID-19 patients who received Dexamethasone, observational and experimental studies on the outcomes use evaluation of Dexamethasone. Exclusion criteria are the articles that do not provide control in controlled studies and do not show clear research results on the use of Dexamethasone. An initial search from four databases by entering keywords resulted in 1,046 articles. After screening articles duplication we obtained 835 studies. Finally, 6 articles were obtained after we screened for the article that it can be obtained its full text and 5 articles joined in articles included in the meta-analysis. The analysis showed that Dexamethasone in Covid-19 patients could reduce the incidence of death within 28 days with RR of 0.78 (95% CI 0.57–0.97 P=0.13) compared with Methylprednisolone, Dexamethasone was compared without corticosteroids with RR 0.89 (95% CI 0.82-0.97 P=0.01). Dexamethasone also reduced mechanical ventilator use during treatment with RR 0.95 (95% CI = 0.86-1.05 P = 0.28) compared without corticosteroids. The conclusion from these results: the use of Dexamethasone can reduce the number of deaths in COVID-19 patients, especially severe and critically ill category patients.